Investigation of binary nanocrystal superlattice - Christine, Kusuma Dewi (2013)
Binary Nanocrystal Superlattice (BNSL) is the assembly of nanoparticles of two different materials. Based on the fact that atoms and molecules can result in various crystal structures and properties, nanocrystal will definitely give an even wider choices of properties due to its size quantum effect. [Peer Assessment Review]